Ð Ð¸Ñ‚Ð¼Ñ–Ñ‡Ð½Ð¸Ð¹ Ð²Ð¿Ð»Ð¸Ð² Ð½Ð¸Ð·ÑŒÐºÐ¸Ñ… Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€ Ð½Ð° Ð¾ÑÐ¾Ð±Ð»Ð¸Ð²Ð¾ÑÑ‚Ñ– Ð²Ñ–Ð»ÑŒÐ½Ð¾Ñ€Ð°Ð´Ð¸ÐºÐ°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð¾ÐºÐ¸ÑÐ»ÐµÐ½Ð½Ñ Ñ‚ÐºÐ°Ð½Ð¸Ð½ ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€ Ð¼Ð¾Ð·ÐºÑƒ - Kotsar, V. L.; Babiychuk, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
After application of rhythmic cold effect (RCE) there were studied the parameters of chemiluminescence and pro-oxidantantioxidant balance in the tissues of rat’s brain. There was noted more manifested change of the parameters in hypothalamus, direct dependences between total light sum S, TBA-active products, induced by lipid peroxidation and the inverse dependence of these parameters and GSH were found.